2016
DOI: 10.1242/jcs.190843
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional in vivo imaging of pancreatic islets during diabetes development

Abstract: Pancreatic islet dysfunction leading to insufficient glucose-stimulated insulin secretion triggers the clinical onset of diabetes. How islet dysfunction develops is not well understood at the cellular level, partly owing to the lack of approaches to study single islets longitudinally in vivo. Here, we present a noninvasive, high-resolution system to quantitatively image real-time glucose metabolism from single islets in vivo, currently not available with any other method. In addition, this multifunctional syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Islet transplantation and in vivo imaging have been described previously 12 . In brief, mouse islets from B6 WT and db/db mice were isolated the day before transplantation and cultured overnight in RPMI 1640 with 10% FBS.…”
Section: Islet Transplantation and In Vivo Imagingmentioning
confidence: 99%
“…Islet transplantation and in vivo imaging have been described previously 12 . In brief, mouse islets from B6 WT and db/db mice were isolated the day before transplantation and cultured overnight in RPMI 1640 with 10% FBS.…”
Section: Islet Transplantation and In Vivo Imagingmentioning
confidence: 99%
“…These and other studies demonstrate the potential of islet intrinsic parameters for the study of islet/beta cell function and survival, namely islet volume, morphology of intra-islet vasculature including vessel diameter and blood vessel integrity (leakage), islet backscatter signal indicating islet integrity and beta cell insulin content, macrophage infiltration, collagen accumulation, cell death, and glucose metabolism indicated by NAD(P)H levels [6] , [7] , [29] , [30] , [31] , [32] , [33] .…”
Section: Pancreatic Islet Transplantation To the Acementioning
confidence: 62%
“…Further, the possibility to study the individual vessel trajectories in relation to tumour volume may www.nature.com/scientificreports/ be highly useful to increase our understanding of PDAC vascularization and how to overcome problems related to drug delivery in these cancers. Although it has been described that islets grafted to the anterior chamber of the eye display AF properties up to 600 nm in vivo 31 , the high signal to noise ratio between islet AF and surrounding pancreatic tissue in the red to the NIR part of the spectrum has to the best of our knowledge not been described previously. In our study, we observed droplet like regions of islet AF over a broad range of the spectrum (excitation maxima tested between 480 and 710 nm).…”
Section: Discussionmentioning
confidence: 85%